Strategi peningkatan keteraturan dan aksesibilitas melalui Addressing di Desa Salak, Kecamatan Talawi, Kota Sawah Lunto - Indra Yeni; Dian Yustika Mora; Given Valentino; Mufid Amafi; Necia Lestari Simangunsong; Salsabila Zakiyah Harahap (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2025)
This research examines the implementation of a house numbering system in Salak Village as an effort to improve administrative order and public service accessibility. Previously, the village faced challenges such as inaccurate population data, logistical difficulties, and obstacles in emergency services. Through a participatory approach, the village government conducted data collection, area mapping, and systematic installation of house numbers. The research results show an increase in public service efficiency, simplification of bureaucratic processes, and the formation of more effective village governance. This house numbering system also serves as a foundation for developing smart village concepts in the future. This finding is expected to be a reference for other villages facing similar problems in improving the quality of public services and village governance. The purpose of this community service is to improve public service accessibility through addressing, namely the creation of house numbers in Salak Village, which is a form of concern for the environment by helping to provide new house address markers. This aims to facilitate data collection and public services, as well as increase efficiency and accuracy in identifying houses. This community service was carried out through socialization methods and data collection of houses that need to be given house numbers. The result is that 350 houses in Salak Village have received house numbers, consisting of 114 houses in Dusun Pulau Ambacang, 86 houses in Dusun Talangung, and 150 houses in Dusun Ibus. The KKN team completed the house numbering process within 1-7 days. The response of Salak Village residents to house numbering was very enthusiastic, as it helped provide complete identity regarding their house addresses. In conclusion, this program produces a work program that is directly beneficial to the community and is well implemented through the Salak Village addressing program.